Identification of the putative ancestral allele of bovine single‐nucleotide polymorphisms. (26th May 2014) - Rocha, D.; Billerey, C.; Samson, F.; Boichard, D.; Boussaha, M.
Summary Identifying the action of natural selection from patterns of standing genetic variation has long been of interest to the population genetic community. Thanks to the availability of large single‐nucleotide polymorphism (SNP) data sets for many species and of high‐throughput SNP genotyping methods, whole‐genomic surveys to detect selective sweeps are now possible. Knowing the ancestral allele increases the power to detect selection. We present here a comparative genomic approach to determine the putative ancestral allele of bovine SNPs deposited in public databases. We analysed 19 551 488 SNPs and identified the putative ancestral allele for 14 339 107 SNPs. Our predicted ancestral alleles were in agreement with ancestral alleles detected by genotyping outgroup species for 97% SNPs from the BovineSNP50 BeadChip. This comparison indicates that our comparative genomic‐based approach to identify putative ancestral alleles is reliable.